COMPREHENSIVE MANAGEMENT OF ORAL FRAILTY IN MULTIPLE SYSTEMIC DISEASES GERIATRIC PATIENT - Novia Tri Hasanah; Riani Setiadhi (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACTBackground Oral frailty is an important geriatric syndrome characterized by decreases in oral function that coincides with declines in cognitive and physical function. Objective: The aim of this case report is to describe the comprehensive management of oral frailty in a medically compromised geriatric patient prior to cardiovascular surgery. Case: A 64-year-old male patient complained of pain in swallowing and sore mouth since two days before. He had multiple systemic diseases, including infective endocarditis, acute kidney injury, type II diabetes mellitus, thrombocytopenia, and electrolyte-fluid imbalance. Extra-oral examination showed lymphadenitis, icteric sclera, and dry-exfoliative lips. Intra-oral examination revealed tongue depapillation, frothy saliva, and dry mucosa with poor oral hygiene. The scraped-off white plaque leaving erythematous area was found on the dorsal and ventral tongue, buccal mucosa, and hard palate. Irregular multiple major ulcers, surrounded by erythema, well-demarcated with yellowish concave base, and covered by thick yellowish-green sputum at the soft palate to the uvula. The diagnosis was exfoliative cheilitis, aphthous-like ulcer, acute pseudomembranous candidiasis, and moderate xerostomia. A D-E-N-T-A-L questionnaire was used to evaluate oral frailty, and the cumulative result was seven. Case Management: The patient was treated with 100% petroleum jelly, 0.12% chlorhexidine digluconate mouthwash, and chlorine dioxide-zinc mouthwash three times a day. The oral lesions showed significant improvement after one week of treatment. Conclusion: Appropriate therapy for oral lesions and eliminating the infection could be considered to minimize the long-term effect of oral frailty. The comprehensive management of oral frailty could be beneficial for improving the quality of life. Keywords: Geriatric, Oral frailty, Oral lesion, Systemic disease